Strategi Peningkatan Hasil Belajar Siswa dalam Permainan Bola Basket Melalui Metode Tutor Sebaya di Kelas XI J SMA Negeri 2 Semarang - Irfan Toni Saputro; Osa Maliki (Journal on Education, 2025)
Physical education has an important role in the physical and psychological development of students. Still, there are often challenges in the learning process that result in low student motivation and participation. This study aims to improve student learning outcomes in basketball games by applying the peer tutor method in class XI J SMA Negeri 2 Semarang. The research method used was classroom action research (PTK) consisting of two cycles, with each cycle involving planning, implementation, observation, and reflection. The results showed that the application of the peer tutor method succeeded in improving the average score of students' practical tests from 74.6 in cycle I to better in cycle II, with an increasing percentage of learning completeness. In conclusion, the peer tutor method is effective in increasing students' motivation and learning outcomes in learning basketball, as well as providing a more interactive and fun learning experience.